Changing environments and human settlement during Mid-Holocene in Rio de Moinhos beach (Esposende Northern Portugal) - Granja, Helena (2016)
This work results from a combination of sedimentological, palaeocological and archaeological data, made available due to special meteo-marine conditions that removed sand from the beach of Rio de Moinhos, exhuming older sedimentary deposits and bringing into evidence a huge amount of archaeological remains Prehistoric and Roman (the latter not considered here). In this paper the relationship between the palaeoenvironments and the contemporary human evidence is analysed. The time interval considered in this study goes from 5590±80 yr BP (4614-4319 cal BC 2) to 3550±30 yr BP (2007-1772 cal BC 2) and encompasses a succession of environments comprising an Alnus forest, a wetland, a brackish lagoon and a fresh water lake, showing a progressively finer and more organic sequence, and higher infilling rates. Initially, in the wetland phase, there are no certain traces of human activity in the pollen content, but from around 4860±30 yr BP (3703-3539 cal BC 2) cereal cultivation and agriculture are detected. Later on indications of grazing also appear. However, human presence is well documented by a lithic assemblage dated from the interval between 5590±80 y BP (4614-4319 cal BC 2) and 4680±30 yr BP (3622-3370 cal BC 2). Another lithic industry predates 5590±80 yr BP, being therefore prior to the Alnus forest. Apparently, it documents the earliest evidence of human presence at the site.